Rear polymineral zone of near-veined metasomatic aureole in mesothermal Zun-Holba gold deposit (Eastern Sayan) - Cherkasova, Tamara Yurievna; Kucherenko, Igor Vasilyevich; Abramova, Raisa Nikolaevna (IOP Publishing, 2015)
Unique data of the mineralogical and petrochemical zoning of near- veined metasomatic aureole of mesothermal Zun-Holba gold deposit are presented and discussed. It was established that mineralogical and petrochemical zoning order is based on Korzhinsky theory describing the differential component mobility. However, the internal polymineral zone structure of metasomatic column in Zun-Holba deposit does not comply with Korzhinsky concept describing the mono-mineral composition of axial (ore-bearing quartz veins) and binary-mineral rear (quartz-sericite) zones. Mineral zoning complication is governed by component diffusion (from fractured fluid to pores) and pulsation mode of metalliferous fluid input into the mineralization area.
Keywords: полиминеральные зоны; метасоматические ореолы; месторождения; Золото; Восточный Саян